Pengaruh Media Video Animasi Powtoon Terhadap Hasil belajar Kognitif Pembelajaran IPA SMP Materi Sistem Peredaran Darah - Yusuf Irawan; Nur Efendi (Jurnal Teknologi Pendidikan, 2025)
This study aims to analyze the effect of the application of Powtoon-based animated video media on cognitive learning outcomes of science learning in junior high schools, especially on the circulatory system material. The sample of this study was conducted in 1 experimental ECP1 class and 1 control ECP2 class in the same school with a total sample of 64 people. This study uses a quantitative approach with a quasi-experimental method: Nonequivalent Time Sample Design. Data collection in this study uses test techniques. Normality Test, Homogeneity Test and T Test (Independent T-Test) will be applied in this study as data processing techniques using the SPSS 26 application. The results of the instrument validation test obtained an average percentage of 87,7%. The results of the normality test with the results of the Pre Test in the Experimental Class 0,156 > 0,05, Post Test in the Experimental Class 0,98 > 0,05. While in the Pre Test in the control class 0,200 > 0,05 and Post Test in the control class 0,200 > 0,05. The results of the Homogeneity Test are 0,822 > 0,05. The results of the T-Test are 0,000 < 0,05, so it can be concluded that the application of Powtoon-based animated video media in the learning outcomes of science learning in junior high schools on the circulatory system material can have an influence on improving students' cognitive learning outcomes. Further researchers should start developing and implementing innovative and adaptive learning media in 21st Century learning.